2021
DOI: 10.18632/aging.203751
|View full text |Cite
|
Sign up to set email alerts
|

Anemoside B4 sensitizes human colorectal cancer to fluorouracil-based chemotherapy through src-mediated cell apoptosis

Abstract: Currently, 5-Fluorouracil (5-FU) based chemotherapy is the primary option for colorectal cancer after surgery, whereas chemotherapy resistance related mortality is observed in a large proportion of patients. Anemoside B4 (AB4) is a triterpene saponin, which exhibits a considerable activity in oncotherapy. In this study, we explored the efficacy of AB4 in FU-based chemotherapy in colorectal cancer cells and the underlying molecular mechanisms. Our results indicated a significant synergistic activity of AB4 in 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…It should be noted that a combination of 5-FU and anemoside B4 was found to be more efficient in suppressing tumor growth (derived from chemotherapy-resistant HCT116 colorectal cell line) than 5-FU given alone (He et al 2021b). This study provides additional experimental data supporting the potential of triterpene saponins as adjuvants in chemotherapy.…”
Section: Triterpene Saponins Active In In Vivo Models Of Breast Cancermentioning
confidence: 61%
“…It should be noted that a combination of 5-FU and anemoside B4 was found to be more efficient in suppressing tumor growth (derived from chemotherapy-resistant HCT116 colorectal cell line) than 5-FU given alone (He et al 2021b). This study provides additional experimental data supporting the potential of triterpene saponins as adjuvants in chemotherapy.…”
Section: Triterpene Saponins Active In In Vivo Models Of Breast Cancermentioning
confidence: 61%
“…Li [32] found that the expression of P-gp protein (drug resistance protein) decreased after treatment with non-toxic dose of AB4, which could reverse the drug resistance of human colon cancer L-OHP resistant cells LoVo / L-OHP. He [33] also found that AB4 inhibited the proliferation of human colon cancer HCT116/5-FU cells in vitro and promoted the apoptosis of mouse drug-resistant colorectal cancer cells HCT11/5-FU in vivo. In addition, the combined treatment of AB4 and 5-FU induced the apoptosis of colorectal cancer cells by phosphorylation of Scr protein kinase and activation of caspase-9.…”
Section: Antitumor Mechanisms Of Ab4mentioning
confidence: 95%